THE EFFECT OF TOPICAL GENTAMYCIN APPLICATION AT THE URETHRAL STENT TO THE URETHRAL STENT’S BACTERIAL COLONY-FORMING-UNIT COUNTS IN HYPOSPADIAS PATIENTS PERFORMED URETHROPLASTY: A PRELIMINARY STUDY - Oetama, Harris; sibarani, jupiter; Tjahjodjati, Tjahjodjati; Agil, Ahmad (Indonesian Journal of Urology, 2018)
Objective: To determine the effect of topical gentamycin application at the urethral stent to the stent’s colony-forming-unit (CFU) in hypospadias patients. Material & methods: This study is a double blind prospective randomized controlled study, conducted from November 2016 - August 2017 in Urology Department Hasan Sadikin Hospital Bandung. We include patients with distal until penoscrotal hypospadias who underwent urethroplasty for the first time. The subjects were divided into 2 groups: Group A were patients performed urethroplasty with nasogastric tube (NGT) urethral stents only. Group B were patients performed urethroplasty with NGT urethral stents that were coated with topical gentamycin. Both group were operated by a single surgeon using either Tubularized Incised Plate (TIP) or Onlay Preputial Flap technique. Both group used supra pubic urinary diversion. Both group were given the same preoperative and postoperative intravenous antibiotics and given same dressing. At post operative day 7, the stents were removed and swabbed for bacterial culture and resistance test and colony-forming-unit (CFU) counts. Demographic data is described and, among others were analyzed statistically. Other adverse events and complications were also documented. Results: There were 25 hypospadias patients who were performed urethroplasty (12 patients in Group A and 13 patients in Group B). The median age in group A was 7 ± 2.995 (years old) and the mean age in group B was 6 ± 3.178  (years old). In group A, 1 patient (8.3%) were distal shaft type, 1 patient (8.3%) were middle shaft type, 8 patients (66.7%) were penoscrotal type, 1 patient (8.3%) were proximal shaft type, and 1 patient (8.3%) were subcoronal type. In group B, 3 patients (23.1.%) were distal shaft type, 3 patients (23.1%) were middle shaft type, 5 patients (38.5%) were penoscrotal type, and 2 patients (15.7%) were proximal shaft type. In group A, 6 patients (50%) using TIP, 6 patients (50%) using onlay preputial flap. In group B, 5 patients (38.5%) using TIP, 8 patients (61.5%) using onlay preputial flap. In Group A, Staphylococus haemoliticus was the most common bacterial found in urethral stent swabbed culture (50%), followed by Pseudomonas aeroginosa (16.7%), Acinetobacter baumannii (8.3%), Enterococcus faecalis (8.3%), Morganella morgagnii (8.3%) and sterile cultures (8.3%). In Group B, 38.5% were sterile urethral stents culture, followed by Staphylococus haemoliticus (30.8%), Enterobacter cloacae (7.7%), Staphylococus warneri (7.7%), Staphylococus epidermidis (7.7%), and Moraxella catarrhalis (7.7%). The most sensitive antibiotics in both group were Amikacin, Gentamycin, Meropenem, Cotrimoxazole, and Cefepime. In group A, 11 patients (91.7%) had >100.000 CFU counts, and 1 patient (8.3%) with no colony found.  In Group B, 2 patients (15.4 %) had >100.000 CFU counts, 6 patients (46.2%) had <100.000 CFU counts, and 5 patient (38.5%) with no colony found. In group A, there were 3 patients (25%) with urethra-cutaneous fistula, 4 patients (33.3%) with hematoma, and 5 patients (38.5%) without any complications. In group B, there were 2 patients (15.4%) with urethra-cutaneous fistula, 3 patients (23.1%) with hematoma and 8 patients (61.5%) without any complication. Using Mann-Whitney U-test, we found a significant difference of CFU counts formation between the two groups (p=0.001). Statistically, the lesser CFU counts found, the lesser complication were developed (p=0.001). Conclusion: Topical gentamycin application at the urethral stents in hypospadias patients performed urethroplasty significantly reduced CFU counts found at the urethral stents and thus reduced the urethra-cutaneous fistula and hematoma formation.